2021
DOI: 10.1002/jmor.21359
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of a complex pore‐canal system in the dermal skeleton ofTremataspis(Osteostraci)

Abstract: Thyestiids are a group of osteostracans (sister-group to jawed vertebrates) ranging in time from the early Silurian to Middle Devonian. Tremataspis is unique among thyestiids in having a continuous mesodentine and enameloid cover on its dermal elements, and an embedded pore-canal system divided into lower and upper parts by a perforated septum. The origin of this upper mesh canal system and its potential homology to similar canal systems of other osteostracans has remained a matter of debate. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(62 citation statements)
references
References 37 publications
17
45
0
Order By: Relevance
“…The emergence of this pore-canal system was the focus of a recent study by Bremer et al (2021), who affirmed its close relation to the partially enclosed canal system formed by modified tubercles in the other thyestiid D. gemmifera . However, that study concluded that it was not possible to determine its homology to inter- and intra-areal canals outside of Thyestiida (Bremer et al, 2021). Furthermore, the study agreed with the notion presented by Gross (1961), that the suggested radial canals in D. gemmifera (Wängsjö, 1946) could not be viewed as homologues to radial canals proper (Stensiö, 1927, 1932) because of their much higher position in the middle layer.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The emergence of this pore-canal system was the focus of a recent study by Bremer et al (2021), who affirmed its close relation to the partially enclosed canal system formed by modified tubercles in the other thyestiid D. gemmifera . However, that study concluded that it was not possible to determine its homology to inter- and intra-areal canals outside of Thyestiida (Bremer et al, 2021). Furthermore, the study agreed with the notion presented by Gross (1961), that the suggested radial canals in D. gemmifera (Wängsjö, 1946) could not be viewed as homologues to radial canals proper (Stensiö, 1927, 1932) because of their much higher position in the middle layer.…”
Section: Introductionmentioning
confidence: 89%
“…This study is based on the same dataset that was in part presented by Bremer et al (2021). All specimens were imaged using propagation phase-contrast synchrotron X-ray micro-computed tomography (PPC-SRµCT) at the ID19 beamline of the European Synchrotron Radiation Facility (ESRF, Grenoble, France).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, through a series of virtual-palaeohistological studies, ossification patterns, growth histories and geometries of muscle attachments are assessed in the humeri of fossil fish and early tetrapods (Sanchez et al, 2012(Sanchez et al, , 2013(Sanchez et al, , 2014(Sanchez et al, , 2016Estefa et al, 2020). Some additional studies also focus on Devonian fossil fish to understand the palaeobiology of the early vertebrates through virtual palaeohistology (Giles et al, 2013;Qu et al, 2015;Vas ˇkaninova ´et al, 2020;Bremer et al, 2021). To date, virtual palaeohistology is extensively employed in studying various aspects of fossil hominids, including diet, dental development, life histoly and taxonomy (Smith et al, 2007;Smith et al, 2010;Tafforeau et al, 2012;Le Cabec et al, 2015;Smith et al, 2015;Smith et al, 2018;Beaudet et al, 2021) (see Table S1 of the supporting information for a list of selected studies applying virtual palaeohistology to fossil vertebrate skeletons).…”
Section: Introductionmentioning
confidence: 99%